Simulation optimisation for nurse scheduling in a hospital emergency department (case study: Shahid Beheshti Hospital). (2016) - Sajadi, Seyed Mojtaba; Ghasemi, Shima; Vahdani, Hashem
Healthcare issues have a special role in the people's lives in most societies. Hospitals are the most important centres of healthcare delivery services. The emergency department (ED) of a hospital is a critical unit as it is related to the life and death of the patients where time plays vital role in patients' health. Also, nowadays the cost of healthcare services is exponentially rising. These are leading hospital managers to offer patients faster services with better quality with concern to hospital limitations. Nurse scheduling has an important effect on time and quality of services. It is usually written by hand by the supervisor of the department. This thesis is proposing mathematical method for nurse scheduling that fulfil the hospital limitations and nurse preferences while minimising the patients' waiting queue time. In order to reach the aforementioned objective, the emergency department of a governmental hospital is simulated by arena and simulated annealing algorithm is applied to find the appropriate schedule. Results show that the waiting time of achieved schedule from proposed algorithm is 18% less than existing schedule.